Familial paraganglioma syndrome: a rare case of secondary hypertension in young patients - Miranda Manrique, Gonzalo (2024)
Paragangliomas are uncommon tumors that originate in the autonomic nervous system and whose clinical manifestations result from excessive catecholamine production. Most of those arising from parasympathetic ganglia are located in the neck and at the base of the skull, along the branches of the glossopharyngeal and vagus nerves. On the other hand, sympathetic paragangliomas occur outside the adrenal, gland along the sympathetic chain. Approximately 75 % of them occur in the abdomen, most of which are functional and present with hypersecretion of catecholamines. These tumors exhibit varying degress of aggressiveness and are characterized by a wide spectrum of hereditary predisposition. In fact, more than one-third exhibit such susceptibility. Five hereditary syndromes have been described, each with different pathogenic variants. Moreover, it is known that there are various genotypic and phenotypic correlations associated with each mutation. We present the case of a 26-year-old female patient, with a five-year history of disease, classified as endocrine hypertension. The patient also had elevated urinary fractionated metanephrine. A contrast-enhanced computed tomography (CT) scan revealed a solid mass in the retroperitoneal space. Additionally, magnetic resonance imaging (MRI) detected bilateral tumors at the cervical level which were not associated with functionality. Surgical intervention was performed on the abdominal mass, and the pathological diagnosis confirmed the presence of a well-defined paraganglioma. Despite the low frequency of these tumors, it is important to take them in account in the differential diagnosis of hypertension, especially in young patients, due to their malignant potential and effects on the cardiovascular system.